Tinjauan Etik Rumah Sakit Berkontribusi Dalam Limbah Makanan - Yen, Liauw Djai; Wea, Brigitta Yuliana; Tholib, Clemarie Natasha; Mai, Roy; Rasyiqah, Fajrina Rizki; Yurike, Vony; Ongga, Leonardo (Universitas Kristen Krida Wacana, 2024)
About a third of the food produced per year is thrown away and becomes food waste, affecting various fields on a global scale. According to Williams and Walton, food waste generated by hospitals is two to three times greater than in other service areas. If this food waste is processed and recycled, it will produce methane and CO2 emissions which will also worsen global warming. The purpose is to review the ethics of hospitals that contribute to food waste. This is a literature study that was carried out using the Pubmed and Google Scholar databases from 2014-2024 with the main keywords